Cara Mengelola Kelas yang Efektif di Sekolah Dasar - Farah Syifa Agustia; Ari Suriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Classroom management is a crucial aspect in primary education that influences the success of the learning process. Teachers as facilitators must create a conducive, orderly classroom environment and be able to encourage active student participation. This study uses a qualitative descriptive approach to explore effective classroom management strategies employed by primary school teachers, including physical classroom arrangement, student behavior management, selection of teaching methods, and utilization of educational technology. The results show that adaptive, inclusive, and student-centered classroom management can improve student motivation, discipline, and learning outcomes. Scientific approaches and participatory classroom management are proven effective in enhancing student engagement and interest in learning. Additionally, the use of digital learning media supports a more dynamic classroom management that aligns with current developments. However, challenges such as student diversity and limited resources still need to be addressed through teacher professional development and policy support. Therefore, strengthening teacher capacity and integrating technology are key to successful classroom management in primary schools to improve the quality of basic education.